THE CRYPTOCURRENCY: how to get it through mining - Sena, Luiz Gustavo Banin de; Dian, Mauricio de Oliveira (Revista Interface Tecnológica, 2020)
Through technological growth and development, many things have changed and improved over time, and when it comes to money, this is no different. Over the years and the growth in the use of digital currency in online services and platforms, it is natural to think that new technologies would appear to ensure that these transactions were carried out in a faster, safer and more private way. Therefore, and with the use of technologies such as Blockchain and cryptography, today we have several types of cryptocurrencies, used as a means of exchange that ensures the validity of transactions in a decentralized manner. Through bibliographic research, this work focuses on presenting a series of concepts about cryptocurrencies, as they are a trend in many online systems today, some different types and how we can obtain them, either by buying them directly or through the mining process.